Prevalence and Age-Related Changes of Corneal Astigmatism in Patients Undergoing Cataract Surgery in Northern China - Zhizhong Wu; Caijuan Liu; Zhimin Chen (Journal of Ophthalmology)
Purpose. To examine the magnitude, orientation, and age-related changes of corneal astigmatism of the eyes before cataract surgery. Setting. Hebei Eye Hospital, Hebei, China. Design. A clinical-based retrospective study. Results. The study consisted of 5662 eyes of 5662 consecutive cataract surgery patients with a mean age of 68.26 ± 10.39 (mean ± standard deviation (SD)) years (range 40 to 97 years), and 59.86% of the patients were women. Mean corneal astigmatism was 0.98 ± 0.76 diopter (D) (range 0.00–9.61 D). Corneal astigmatism of 0.50–0.99 D was the most common range of values (30.08%), followed by 1.00–1.49 D (22.15%), ≤0.50 D (21.21%), and 1.50–1.99 D (10.28%). There was a strong U-shaped relation between corneal astigmatism and age (p for nonlinearity <.01). With the increase of age, the astigmatism axis gradually changes from with-the-rule (WTR) to against-the-rule (ATR). Moreover, in young patients with age below 65 years, WTR astigmatism was negatively correlated with age, while ATR was positively correlated with age (r = −0.11, p=.001; r = 0.10, p=.010, respectively). However, in the old patients with age above and equal to 65 years, all types of astigmatism were positively correlated with age. Conclusion. This study may provide valuable and practical information to surgeons when selecting the appropriate surgical method and toric intraocular lens (IOLs).